Charging System for Lead Acid Battery and Capacitor Bank with Ant Colony Optimization - Muslimin, Selamet; Rifaldi, Muhammad Arya; Rahman, A. (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
In the modern era, characterized by an increasing demand for mobility and energy efficiency, fast-charging technology plays a crucial role. As the use of electronic devices and electric vehicles continues to rise, the need for more efficient and energy-saving charging systems is also growing. One of the key components in these systems is the lead-acid battery and capacitor bank, both of which have the ability to store and release energy quickly. Therefore, these components are essential in enhancing the effectiveness of the charging process. However, a major challenge in fast charging systems is optimizing the configuration of lead-acid batteries and capacitor banks to minimize charging time while reducing power losses during the process. Addressing this challenge requires an intelligent approach to determining the optimal power distribution path to ensure a stable and efficient charging process. This study utilizes the Ant Colony Optimization (ACO) algorithm to optimize the configuration of lead-acid batteries and capacitor banks in a fast-charging system. The natural behavior of ant colonies inspires the ACO algorithm to search for the shortest path to a food source. This method has been proven effective in solving various complex optimization problems, including power distribution and energy charging. By implementing this algorithm, the system can identify an optimal charging pattern, reducing voltage fluctuations and maximizing energy efficiency throughout the charging process. The primary goal of this research is to develop a fast charging system that is more efficient, energy-saving, and capable of operating optimally under various conditions. By optimizing the use of lead-acid batteries and capacitor banks through the application of the ACO algorithm, this system is expected to accelerate the charging process without compromising reliability and battery lifespan. The findings of this study are anticipated to contribute to the advancement of smarter charging technology, supporting high mobility needs in the modern era, and providing a more sustainable solution for energy management.